Effects of maternal fructose intake on the offspring’s kidneys - Argeri, Rogério; Nishi, Erika Emy; Kimura Lichtenecker, Débora Conte; Gomes, Guiomar Nascimento (Frontiers in Physiology, 2022)
Fructose overload is associated with cardiovascular and metabolic disorders. During pregnancy, these alterations may affect the maternal environment and predispose offspring to diseases. Aims: To evaluate the renal morphology and function of offspring of dams that received fructose overload during pregnancy and lactation. Methods: Female Wistar rats were divided into the control (C) and fructose (F) groups. C received food and water ad libitum, and F received food and d-fructose solution (20%) ad libitum. The d-fructose offer started 1 week before mating and continued during pregnancy and lactation. The progeny were designated as control (C) or fructose (F); after weaning, half of the F received water to drink (FW), and half received d-fructose (FF). Blood pressure (BP) and renal function were evaluated. The expression of sodium transporters (NHE3-exchanger, NKCC2 and NCC-cotransporters, and ENaC channels) and markers of renal dysfunction, including ED1 (macrophage), eNOS, 8OHdG (oxidative stress), renin, and ACE 1 and 2, were evaluated. CEUA-UNIFESP: 2757270117. The FF group presented with reduced glomerular filtration rate and urinary osmolarity, increased BP, proteinuria, glomerular hypertrophy, macrophage infiltration, and increased expression of transporters (NHE3, NCC, and ENaC), 8OHdG, renin, and ACE1. The FW group did not show increased BP and renal functional alterations; however, it presented glomerular hypertrophy, macrophage infiltration, and increased expression of the transporters (NHE3, NKCC2, NCC, and ENaC), renin, and ACE1. These data suggest that fructose overload during fetal development alters renal development, resulting in the increased expression of renin, ACE1, and sodium transporters, thus predisposing to hypertension and renal dysfunction.